Case study on food processor for Philip's company / Nurul Haszirah Hashim - Hashim, Nurul Haszirah (2022)
The company that chosen by me is Philips’s company. This case study begins with an introduction for Philips’s company with their background history of the company. Then, the organizational structure, product and services, technology and business, marketing and operational strategy company. Next, this study will analyse using SWOT analysis. At the end of this case study, I had provided the finding and discussion to solve the problem and also the recommendation and improvement for the company to improve their quality of the product to make a high demand. Lastly, for the conclusion that I can get from this case study about analysis of the company’s product.